1999
DOI: 10.1021/ac981443c
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Automated Isocratic and Gradient Nano-Liquid Chromatography and Capillary Electrochromatography

Abstract: An automated liquid nano-separation system has been developed for nano-liquid chromatography (nano-LC) and capillary electrochromatography (CEC) using both isocratic and gradient elution. One fused-silica nanocolumn, typically 75 μm i.d. × 39 cm (25 cm effective packed length), packed with Spherisorb ODS 1, 3 μm particle size, can be used with either technique without having to remove the column upon switching from one mode to the other. The mobile phase is delivered by two reciprocating micro-LC pumps at a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 36 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…13 In the latter case the chromatographic support is immobilised by chemical bonding to the capillary walls, but with all other packing methods a retainer is necessary to keep the particles inside the column. This can be accomplished either by modification of the capillary design using tapered capillaries as described recently 14 or through the use of frits, which can be inserted into the column mechanically, 15 or generated inside the capillary by various chemical or physical means. In the literature published so far, the latter method is still the most widely used and a number of techniques for the preparation of frits have been described.…”
Section: Introductionmentioning
confidence: 99%
“…13 In the latter case the chromatographic support is immobilised by chemical bonding to the capillary walls, but with all other packing methods a retainer is necessary to keep the particles inside the column. This can be accomplished either by modification of the capillary design using tapered capillaries as described recently 14 or through the use of frits, which can be inserted into the column mechanically, 15 or generated inside the capillary by various chemical or physical means. In the literature published so far, the latter method is still the most widely used and a number of techniques for the preparation of frits have been described.…”
Section: Introductionmentioning
confidence: 99%
“…The pre-split injection design was first presented 1994 by Behnke and Bayer [85], then by Eimer et al [86], and was further developed by Huber et al [87], Kitagawa et al [88], and Zhang et al [89]. Later, optimized setups, e.g., with autosampler, minimized dead volume, in-line filters to prevent clogging, and outlet restrictor capillary to prevent bubble-formation were presented by Taylor et al [90,91] (similar to the Unimicro [92] starter kit configuration shown in Figure 10.b), Behnke and Metzger [93], Strickmann et al [94], and Alexander et al [95]. Nearly all publications demonstrated the importance of an optimized design of the capillary column inlet device which is schematically shown in Figure 7.a.…”
Section: Pressurizable Gradient Chplc/(p)cec Systems With Pre-split Imentioning
confidence: 99%
“…Alexander et al [6] have assembled a modular system that could be operated in the CEC or nano-pLC mode. With this instrument, gradient elution was possible in both modes.…”
Section: Introductionmentioning
confidence: 99%